1995
DOI: 10.1144/gsl.sp.1995.087.01.05
|View full text |Cite
|
Sign up to set email alerts
|

Detailed geological studies of hydrothermal fields in the North Atlantic

Abstract: Sidescan sonar and TV/photo surveys, TV-controlled sulphide grab sampling and sediment sampling have been carried out at the TAG and MARK hydrothermal fields of the Mid-Atlantic Ridge during research cruises of the Sevmorgeologija Association, St Petersburg. Detailed mapping of the MARK field (23°N) allowed contouring of the massive sulphide bodies. The largest of them are Cu-enriched and the smallest zincenriched. Sulphides of the TAG field (26°N) active mound appear to be Cu-rich in its central and Zn-rich i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 21 publications
1
39
0
2
Order By: Relevance
“…Rona and others (1987) investigated serpentinite outcrops near the 15°20 0 Fracture Zone at the Mid-Atlantic Ridge (MAR) and found evidence of hydrothermal activity influenced by serpentinization reactions. The later discovery of the ultramafic-hosted Logatchev (Batuyev et al, 1994;Bogdanov et al, 1995;Krasnov et al, 1995) and Rainbow (Fouquet et al, 1997) hydrothermal fields on the MAR showed that mid-ocean ridge hydrothermal vents are not exclusively basalt-hosted. Both fields support sulfide chimneys venting acidic (pH $ 2-3), high temperature (up to 360°C) fluids that are significantly enriched in magmatic volatiles (e.g., CO 2 = 10-16 mM) Douville et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Rona and others (1987) investigated serpentinite outcrops near the 15°20 0 Fracture Zone at the Mid-Atlantic Ridge (MAR) and found evidence of hydrothermal activity influenced by serpentinization reactions. The later discovery of the ultramafic-hosted Logatchev (Batuyev et al, 1994;Bogdanov et al, 1995;Krasnov et al, 1995) and Rainbow (Fouquet et al, 1997) hydrothermal fields on the MAR showed that mid-ocean ridge hydrothermal vents are not exclusively basalt-hosted. Both fields support sulfide chimneys venting acidic (pH $ 2-3), high temperature (up to 360°C) fluids that are significantly enriched in magmatic volatiles (e.g., CO 2 = 10-16 mM) Douville et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Only five of the known hydrothermal sites located between 10°and 40°N along the Mid-Atlantic Ridge (MAR), Rainbow, Logatchev, Ashadze, Lost City and Saldanha, are hosted by variable mixtures of serpentinized peridotite and mafic material and are characterized by vent fluid chemistries distinct from those in basaltic environments (e.g., Rona et al, 1987;Krasnov et al, 1995;Donval et al, 1997;Douville et al, 1997;Sagalevich et al, 2000;Holm and Charlou, 2001;Kelley et al, 2001;German and Von Damm, 2003;Baker and German, 2004;Kelley et al, 2005). The discovery of these peridotitehosted hydrothermal systems has stimulated intense interest in the role of serpentinization in crustal aging processes and global geochemical fluxes in ridge and subduction zone environments.…”
Section: Introductionmentioning
confidence: 99%
“…Isotopic investigations have shown that such serpentinized peridotites, similar to altered MORB, are the products of high-temperature and -pressure reactions between peridotite and seawater Taylor 1971, 1973;Sakai and Tsutsumi 1978). Hydrothermal alteration of peridotite was studied experimentally (Seyfried and Dibble 1980;Hajash and Chandler 1981;Janecky and Seyfried 1986) even before the discovery of natural peridotite-hosted hydrothermal vents at Logachev field (Krasnov et al 1995). Reactions between peridotite and seawater under high temperature and pressure have also been examined in batch-type experiments (see Chap.…”
Section: 2mentioning
confidence: 99%
“…Hydrogenenriched hydrothermal fluids are common in such peridotitedominated slow-spreading ridge settings (Kelley et al 2001;Früh-Green et al 2004). Since the first discovery of natural peridotite-hosted hydrothermal vents with abundant H 2 at Logachev field on the Mid-Atlantic Ridge in 1995 (Krasnov et al 1995), other peridotite-hosted and -associated hydrothermal vents have been found, namely, the Rainbow, Nibelungen, Lost City, and Achaze fields on the MidAtlantic Ridge (Charlou et al 1998(Charlou et al , 2008Douville et al 2002;Kelley et al 2005;Melchert et al 2008) and the Kairei field on the Central Indian Ridge (Van Dover et al 2001). A pronounced feature of peridotite-hosted systems is the presence of hydrothermal solutions enriched not only in H 2 but also in CH 4 and other hydrocarbons .…”
mentioning
confidence: 99%